Hydrothermal synthesis of fine bismuth titanate powders - Pookmanee P. (2014)
Bismuth titanate (Bi4Ti3O12) fine powders were synthesized from a low temperature hydrothermal method. Bismuth nitrate and titanium isopropoxide were used as the starting materials with the mole ratio of Bi:Ti = 4:3. Sodium hydroxide was added to adjust the pH of the mixed final solution at 13. The temperature of reaction in the hydrothermal Teflon-lined vessel was 150°C. The effect of reaction time at 5, 10, and 15h was investigated. The phase structure was identified by X-ray diffraction (XRD) technique. Orthorhombic structure of Bi4Ti3O12 fine powders was obtained without calcination step. The morphology and microstructure were investigated by scanning electron microscopic (SEM) technique. The powders were generally sphered in shapes and the average sizes were 0.50-1.20 μm. © 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.